Leiomyosarcoma of the head and neck: A 17‐year single institution experience and review of the National Cancer Data Base. Issue 4 (29th December 2017) - Workman, Alan D.; Farquhar, Douglas R.; Brody, Robert M.; Parasher, Arjun K.; Carey, Ryan M.; Purkey, Michael T.; Nagda, Danish A.; Brooks, John S.; Hartner, Lee P.; Brant, Jason A.; Newman, Jason G.
Abstract: Background: Leiomyosarcoma is a rare neoplasm of the head and neck. The purpose of this study was to present our single‐institution case series of head and neck leiomyosarcoma and a review of cases in the National Cancer Data Base (NCDB). Methods: Patients with head and neck leiomyosarcoma at the University of Pennsylvania and in the NCDB were identified. Demographic characteristics, tumor factors, treatment paradigms, and outcomes were evaluated for prognostic significance. Results: Nine patients with head and neck leiomyosarcoma from the institution were identified; a majority had high‐grade disease and cutaneous leiomyosarcoma, with a 5‐year survival rate of 50%. Two hundred fifty‐nine patients with leiomyosarcoma were found in the NCDB; macroscopic positive margins and high‐grade disease were associated with poor prognosis ( P < .01), and positive surgical margins were related to adjuvant radiation ( P < .001). Conclusion: Head and neck leiomyosarcoma presents at a high grade and is preferentially treated with surgery. Several demographic and tumor‐specific factors are associated with outcomes and prognosis.